Sistema RFID complementar de piso tátil para localização de deficientes visuais em ambientes fechados - Araujo, Renato Pereira de (2015)
For the visually impaired, identify which path to follow to reach the desired destination without assistance from healthy people is a challenge. To move in an unknown environment is required to interact with the mechanisms of information. However the visually impaired do not yet have a navigation system in indoor environments with real-time response that allows this this communication. This paper presents a device that allows interaction with the tactile floor to aid navigation and orientation. Through an audio interface, the device provides the visually impaired relevant information on the space around it and the navigation options available. The relevant information is disseminated using labels with radio frequency identification technology, integrated into a microcontroller and an audio playback card. Each label has an electronic product code that allows to identify it uniquely. The label installed in a standard place of tactile floor is linked to an audio file with information about the space and the available routes. The reader integrated development board reads the labels and sends the electronic code to the microcontroller, which in turn identifies the code and assigns this audio file to be played. The device was tested by a volunteer who found all labels positioned on the floor tactile alert, clearly identified its position and reached the desired destination without route errors. Used as a complement to tactile signage, this device provides an interaction between the visually impaired and the existing tactile signage. This project will directly contribute to society, providing a convenient navigation system for people with visual disabilities have greater autonomy